Yes, that is correct! The equation that can be used to solve for m∠C is 22° + m∠C = 90°.
To solve for m∠C, you can start by subtracting 22° from both sides of the equation:
22° + m∠C - 22° = 90° - 22°
This simplifies to:
m∠C = 68°
So, m∠C is equal to 68°.
In a diagram, ∠A and ∠B are vertical angles, and ∠B is a complementary angle with ∠C. If m∠A=22°, write an equation that you can use to solve for m∠C.(2 points)
Since ∠A and ∠B are vertical angles, they are congruent, so m∠A = m∠B.
Since ∠B is a complementary angle with ∠C, we know that m∠B + m∠C = 90°.
Using the fact that m∠A = 22°, we can substitute m∠A for m∠B in the second equation to get:
22° + m∠C = 90°
This is the equation we can use to solve for m∠C.
help!!!!
1 answer